A Mn3O4 nano-wall array based binder-free cathode for high performance lithium–sulfur batteries. Issue 14 (15th March 2017) - Guo, Junling; Zhang, Xiaolong; Du, Xinyu; Zhang, Fengxiang
Abstract : Nano-sheet array structured, highly stable Mn3 O4 (compared with MnO2 ) provides long-lasting suppression of polysulfide shuttle in lithium sulfur batteries. Abstract : Lithium–sulfur batteries (LSBs) have recently attracted great interest owing to their high theoretical energy density (2500 kW kg −1 ) and low cost and the environmental friendliness of sulfur as the active species at the cathode. However, rapid capacity fading restricts practical application of LSBs. Despite the encouraging progress achieved, this issue still needs to be further addressed. Herein, we report a novel cathode structure based on nano-wall-array Mn3 O4 which shows excellent cycle and rate performances. In such a cathode, the Mn3 O4 nano-wall arrays function as "nano reservoirs" for sulfur confinement so that the cathode can yield a high-rate (2C) initial (∼593 mA h g −1 ) and reversible capacity (∼355 mA h g −1, 60% retention after 3000 cycles). We also show, by X-ray photoelectron spectroscopic and electrochemical analyses, that Mn3 O4 as a sulfur-hosting oxide is better than conventionally used MnO2 ; this is because the former shows better chemical stability in the electrolyte when binding with polysulfides, giving rise to long-lasting suppression of polysulfide shuttle. Our work demonstrates that building a nano-wall array structure of Mn3 O4 is an effective strategy to improve lithium–sulfur cathode performance, and for the first time, we propose and show that the stability of polar materials in the electrolyte is a crucial factor that determines the cycle performance of polar materials/S electrodes.